Integration of Local Wisdom of Pencak Silat in Learning Newton's Laws based on ICT-Technology to determine Student Learning Motivation - Azar Zakaria; Muhammad Satriawan; Rahmatta Thoriq Lintangesukmanjaya; Utama Alan Deta; Khoirun Nisa' (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This research aims to develop a 2D technological visualization that integrates the application of Newton’s Third Law into pencak silat movements, providing a contextual bridge between physics concepts and traditional martial arts. The objective is to enhance students’ motivation and conceptual understanding by presenting the action–reaction principle through culturally relevant motion analysis. Method: The study employed a qualitative descriptive method with data collected from literature analysis and expert interviews involving pencak silat practitioners and physics educators. The visualization design was then refined to display key pencak silat techniques such as stances, strikes, and blocks—while mapping the corresponding forces of action and reaction.  Results:  2D visualization is effective in clarifying how Newton’s Third Law operates within martial movements, making abstract concepts more tangible. Teachers and students reported that the visualization improved comprehension, engagement, and learning motivation. Moreover, the concise two-dimensional format allowed force interactions to be represented clearly without overwhelming detail, supporting efficient classroom integration.  Novelty: This research lies in merging local cultural heritage with interactive technological media, transforming pencak silat not only as a form of art and self-defense but also as an innovative educational tool for learning physics. This approach highlights how digital visualization can preserve tradition while modernizing science education, thus offering a meaningful model for contextual and technology-enhanced learning